Manajemen Sumber Daya Manusia Dalam Meningkatkan Kinerja Guru Sekolah Dasar Islam: Human Resource Management in Improving the Performance of Islamic Elementary School Teachers - Ansori, Ahmad (STAI Publisistik Thawalib Jakarta, 2024)
Improving human resource performance through optimal management, such as placement, training, and evaluation, is a key factor in enhancing service quality in educational institutions and supporting the achievement of educational goals and national development. This study aims to explore the strategies employed by the school principal in managing human resources to improve teacher performance at Azzuhra Integrated Islamic Elementary School Pekanbaru. The research method used is a qualitative descriptive approach. Data collection was carried out using three techniques: observation, interviews, and documentation. Meanwhile, data analysis was conducted in several stages, including data collection, data reduction, data presentation, and finally, drawing conclusions. The results showed that: planning includes analyzing needs and recruiting teachers periodically based on the school’s requirements. Organizing involves placing teachers according to their competencies and providing clear job descriptions. Implementation includes task execution, rewarding outstanding teachers, and applying educational punishment for violators. Supervision is carried out through routine control of teachers' performance, and evaluation is conducted periodically to assess the effectiveness of teachers’ tasks. The follow-up to the evaluation is the improvement of teacher training and competency development.